Prehospital plasma transfusion versus standard of care following traumatic injury: a review of the systematic reviews and a meta-analysis - Ayman El-Menyar (440103) (2025)
Background Individual studies suggest that administering prehospital blood products such as plasma to injured patients is feasible, may lower mortality, and improve coagulation. By compiling all existing evidence, we aimed to investigate whether prehospital plasma (PHP) transfusion can be safely administered and improve the clinical outcomes of trauma patients. Methods A systematic review (SR) and meta-analysis were conducted in accordance with the PRISMA guidelines to assess the effectiveness and safety of PHP transfusion compared to the standard of care in trauma patients. A literature search (2012 and 2024) was performed in PubMed, MEDLINE, EMBASE, and the Cochrane Library using the terms: “plasma resuscitation,” “prehospital plasma,” “prehospital blood components,” “emergency transfusion,” “trauma hemorrhage management,” “lyophilized plasma,” “freeze-dried plasma " “LyoPlas,” FlyPlas,” and “thawed fresh frozen plasma .“Studies focused on pediatric patients, in-hospital settings, feasibility only, or non-plasma interventions were excluded. Primary outcomes included early (24 hours) and late (28 or 30 days) mortality, and secondary outcomes included 24-hour transfusion units, vasopressor use, multiple organ failure, transfusion reaction, acute lung injury, and sepsis. The quality of studies was assessed using the Newcastle-Ottawa Scale and the Cochrane Risk of Bias tool. The review was registered with PROSPERO. Sensitivity analyses were performed, excluding small studies with high variance and studies with combined blood products. Results Twelve studies comprising 3,193 trauma patients (1,579 intervention and 1,614 control arm) and seven SRs were included. There was no significant difference between the PHP and control groups for early and late mortality; however, the sensitivity analysis favored the PHP transfusion for 24-hour mortality. Without statistical significance, the total 24-hour volume of RBC units and vasopressor use was lower in the PHP group than in the controls. There was no significant difference between the PHP transfusion and control groups for the incidence of organ failure, adverse events, transfusion reactions, and sepsis. Observational studies were mostly of good quality, with two studies showing a moderate risk of bias. In contrast, RCTs had some concerns but were generally at a low risk for most domains. Conclusion The overall pooled analysis revealed no significant benefit to PHP transfusion in trauma patients; however, sensitivity analyses showed a significant association of PHP and lower 24-hour mortality. PHP did not significantly decrease vasopressor use or late mortality; however, it may reduce the total use of RBCs in the first 24 h. Regarding safety, the review findings should be interpreted cautiously. Umbrella review was not conducted due to the heterogeneity and inconsistent inclusion criteria and outcomes. Further studies are needed to address the inconsistency in the existing evidence and determine whether PHP transfusion should be recommended for trauma patients with clearer and standardized endpoints and adverse event reporting. Other Information Published in: European Journal of Trauma and Emergency Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00068-025-03033-z